One Gate System : Inovasi Digital Industri Berbasis Budaya pada Komunitas Batik Tulis Karangploso Kabupaten Malang - Hikmawati, Rosyidatul; Zakiyah, Millatuz; Fajar, Yusri; Wijayanti, Jamila (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Hand-drawn batik is a rich Indonesian cultural heritage with unique and beautiful characteristics. Currently, hand-drawn batik has become a cultural industry that needs to be empowered. In the face of digitalization, innovative steps are needed to maintain the sustainability and growth of this industry. This project aims to develop the hand-drawn batik cultural industry through digital innovation to ensure that hand-drawn batik remains relevant and continues to grow. This innovation is implemented by utilizing digital technology to expand the marketing reach of the hand-drawn batik industry. The One Gate System is a digital innovation designed to accommodate the marketing of hand-drawn batik production within the batik-making community in Karangploso Sub-district, Malang. This sub-district has 13 batik-making groups that mass-produce hand-drawn batik with the distinctive identity of Karangploso and rich philosophical meanings. With the One Gate System, the local cultural value and sales reach of batik continue to increase.